Ventilatory effects of 8 h of isocapnic hypoxia with and without beta-blockade in humans. - Clar, C; Dorrington, K; Robbins, P (1999)
This study investigated whether changing sympathetic activity, acting via beta-receptors, might induce the progressive ventilatory changes observed in response to prolonged hypoxia. The responses of 10 human subjects to four 8-h protocols were compared: 1) isocapnic hypoxia (end-tidal PO2 = 50 Torr) plus 80-mg doses of oral propranolol; 2) isocapnic hypoxia, as in protocol 1, with oral placebo; 3) air breathing with propranolol; and 4) air breathing with placebo. Exposures were conducted in a chamber designed to maintain end-tidal gases constant by computer control. Ventilation (VE) was measured at regular intervals throughout. Additionally, the subjects' ventilatory hypoxic sensitivity and their residual VE during hyperoxia (5 min) were assessed at 0, 4, and 8 h by using a dynamic end-tidal forcing technique. beta-Blockade did not significantly alter either the rise in VE seen during 8 h of isocapnic hypoxia or the changes observed in the acute hypoxic ventilatory response and residual VE in hyperoxia over that period. The results do not provide evidence that changes in sympathetic activity acting via beta-receptors play a role in the mediation of ventilatory changes observed during 8 h of isocapnic hypoxia.